Asymmetric Information on Noncognitive Skills in the Indian Labor Market : An Experiment in Online Job Portal - Yamauchi, Futoshi; Nomura, Shinsaku; Imaizumi, Saori; Areias, Ana; Chowdhury, Afra (World Bank, Washington, DC, 2018)
This paper examines the impact of noncognitive (socio-emotional) skills on job market outcomes, using a randomized control trial implemented in an online job portal in India. Job seekers who registered in the portal were asked to take a Big-Five type personality test and, for a random subsample of the test takers, the results were displayed to potential employers. The outcomes are measured by whether a potential employer shortlisted a job seeker by opening (unlocking) his/her application and background information. The results show that the treatment group for whom test results were shown generally enjoyed a higher probability of unlock. That is, employers are more interested in those for whom they can see personality test results. Such a relationship was not seen in the pre-test period, which confirms that the results are unlikely to be spurious. The study also finds a significant impact among organized, calm, imaginative, and/or quiet applicants (no effect is detected among easy-going, sensitive, realistic, and/or outgoing applicants), which seems to display employers' preference.